Implementation of Islamic Psychoeducational Counseling to Overcome Learning Problems in Students of PAB 9 Patumbak High School - Matius Ocon Ginting; Anwar Saputra Siregar; Mutiara Raihan Daniyah Lubis; Neng Nurcahyati Sinulingga (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
This study investigates the use of Islamic psychopedagogical counseling to overcome student learning issues, including test anxiety and difficulty controlling learning routines, in Islamic-based private high schools. Data were gathered using qualitative case study methodologies, which included interviews, observations, and document analysis. The findings revealed that counselors employed spiritually integrated psychopedagogical strategies such as psychopedagogy, guided reflection, dzikr practice, prophetic tales, and reflective activities (muhasabah). This approach aided in spiritual reframing, allowing pupils to see scholastic difficulties as part of tarbiyah ruhaniyah rather than as proof of failure. As a consequence, students' attitudes about learning improved, including lower academic anxiety, more emotional control, and increased learning engagement. Despite the cultural taboo associated with counseling services, contextual strategies received initial good responses. This study highlights Islamic psychopedagogical counseling as a contextually relevant framework for supporting student learning experiences in Islamic educational settings.